A discrete choice experiment with health professions trainees to improve the urban-rural health care access disparity in Appalachia: Study protocol - Chris Gillette; Jan Ostermann; Sarah Garvick; Chris Everett; Dawn Caviness; Aylin A. Aguilar (PLoS ONE, 2025)
Globally, those who live in rural areas experience significant barriers to accessing health care due to a maldistribution of health care providers. Those who live in rural areas in the Appalachian region of the United States face one of the worst shortages of health care providers despite experiencing more complex health needs compared to Americans in more affluent, urban areas. Prior research has failed to identify effective solutions to narrow the provider maldistribution, despite it being a policy focus for decades. More work is needed to better understand the complex, multidimensional process in which health care providers select jobs and how job, community, and providers’ intrapersonal characteristics influence job selection. This paper is a protocol for a study aimed at identifying effective policies and incentives to improve recruitment of healthcare providers for their first job in rural Appalachia. We will use rigorous, theoretically grounded discrete choice experiment methodology (DCE) to accomplish the study’s objective. The main outcome will be the relative importance of alternative community and job characteristics for trainees’ choices of jobs in rural Appalachia. secondary outcomes of interest will be trade-offs that these trainees make when selecting a job, described in the form of marginal rates of substitution (mRS). Participants include medical residents and fellows, PA students and NP students in their final year of training. The choice context will be the recruitment of these trainees for their first job. Data will be analyzed using mixed logit analysis. Results from this DCE will improve our understanding of the job selection process for health care providers. The identification and prioritization of predictors of trainees’ rural job choices will allow for the development of policies and incentives that will enable policymakers and health care systems to recruit more providers to rural and underserved areas.